Предмет: Алгебра, автор: brovinnndima

помогите пожалуйста ​

Приложения:

Ответы

Автор ответа: ludmilaksenija2005
0

Объяснение:

13 а.

(-2,5)^2+1,5^2=(-5/2)^2+(3/2)^2=25/4+9/4=

=34/4=17/2

б) (-2/3)^4-(2/9)^2=16/81-(2/9)^2=

=16/81-4/81=12/81=4/27

Автор ответа: Sacha2015
0

Ответ:

а)8,5

б)\frac{12}{81}

Объяснение:

а) (-2,5)^{2} + 1,5^{2} = ((-2,5)*(-2,5)) + (1,5*1,5)= 6,25+2,25=8,5

б)(-\frac{2}{3})^{4}  - (\frac{2}{9})^{2} = ((-\frac{2}{3})*(-\frac{2}{3})*(-\frac{2}{3})*(-\frac{2}{3})) - (\frac{2}{9} *\frac{2}{9} )= \frac{16}{81} -\frac{4}{81} = \frac{12}{81}

Похожие вопросы